2009
DOI: 10.2478/s11658-009-0010-8
|View full text |Cite
|
Sign up to set email alerts
|

Interactions between canthaxanthin and lipid membranes — possible mechanisms of canthaxanthin toxicity

Abstract: Canthaxanthin (β, β-carotene 4, 4' dione) is used widely as a drug or as a food and cosmetic colorant, but it may have some undesirable effects on human health, mainly caused by the formation of crystals in the macula lutea membranes of the retina. This condition is called canthaxanthin retinopathy. It has been shown that this type of dysfunction of the eye is strongly connected with damage to the blood vessels around the place of crystal deposition. This paper is a review of the experimental data supporting t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
18
0
6

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(25 citation statements)
references
References 54 publications
1
18
0
6
Order By: Relevance
“…The angle of 47º at 2 mol% of canthaxanthin was measured, which implies the possibility that canthaxanthin incorporated into lipid membranes can be distributed in such a way that its small fraction can be oriented parallel to the plane of the lipid membrane. This indicated that canthaxanthin is similar to other macular pigment -lutein which parallel orientation has been proposed previously (Sujak et al, 1999;Sujak et al, 2005;Sujak, 2009); for review on other carotenoids see: Gruszecki, 2009. Canthaxanthin toxicity towards the macula lutea lipid membranes can result from its very strong molecular interactions with the lipid molecules of different structures. Several of them are listed below.…”
Section: Overview Of the Experimental Datasupporting
confidence: 76%
See 1 more Smart Citation
“…The angle of 47º at 2 mol% of canthaxanthin was measured, which implies the possibility that canthaxanthin incorporated into lipid membranes can be distributed in such a way that its small fraction can be oriented parallel to the plane of the lipid membrane. This indicated that canthaxanthin is similar to other macular pigment -lutein which parallel orientation has been proposed previously (Sujak et al, 1999;Sujak et al, 2005;Sujak, 2009); for review on other carotenoids see: Gruszecki, 2009. Canthaxanthin toxicity towards the macula lutea lipid membranes can result from its very strong molecular interactions with the lipid molecules of different structures. Several of them are listed below.…”
Section: Overview Of the Experimental Datasupporting
confidence: 76%
“…It has been proposed that the toxicity of canthaxanthin towards lipid membranes is the result of the strong interaction between the pigment and lipid molecules and of the formation of crystalline aggregates of canthaxanthin in the membranes (for review see: Sujak, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…A cantaxantina geralmente se integra à membrana em orientação vertical, de modo que suas regiões polares e apolares coincidam com as dos fosfolipídeos. A ligação entre a cadeia polieno e as cadeias alquil dos fosfolipídeos se dá por interações de Van der Waals e favorecem a conformação estendida dos fosfolípideos, aumentando a espessura do core hidrofóbico da membrana (Sujak, 2007(Sujak, , 2009(Sujak, , 2012; Gruszecki e Strzalka, 2005).…”
Section: Resultsunclassified
“…As porções polares se unem por ligações de hidrogênio entre os grupos cetona da cantaxantina e o grupo carbonila da cabeça polar dos fosfolipídeos, resultando em imobilização dos grupos fosfato que pode resultar em agregação de vesículas. São notadas alterações das propriedades térmicas da membrana resultando em maior fluidez e a permeabilidade da membrana a solutos polares é reduzida (Sujak, 2007(Sujak, , 2009(Sujak, , 2012; Gruszecki e Strzalka, 2005).…”
Section: Resultsunclassified
“…Finally, in a review paper the authors concluded that all the results of the experiments performed on model systems indicated a very strong effect of canthaxanthin on the physical properties of lipid EFSA Journal 2010; 8(10):1852 membranes, which may explain its toxic action, which leads to the further development of canthaxanthin retinopathy (Sujak, 2009).…”
Section: In Vivo Animal Studiesmentioning
confidence: 99%